Analisis Perbandingan Routing Loops antara OSPF dan EIGRP Menggunakan Spanning Tree Protocol - Wijayanto, Febri; Santoso, Banu (AI Society & STMIK Indonesia, 2024)
This study analyzes the quality of service (QoS) in routing loops between Open Shortest Path First (OSPF) and Enhanced Interior Gateway Routing Protocol (EIGRP) using Spanning Tree Protocol (STP) to prevent loops in network topology. OSPF uses a link-state algorithm, while EIGRP combines link-state and distance vector algorithms. Routing loops can cause network congestion and communication disruptions. Four routing scenarios on IPv6 were tested. Results show that EIGRP without STP yields a throughput of 93.973 Bytes with a delay of 0.147ms, while OSPF without STP yields 94.056 Bytes with a delay of 0.180ms. EIGRP with STP produces a throughput of 93.922 Bytes with a delay of 0.150ms, and OSPF with STP produces 94.056 Bytes. STP implementation improves OSPF delay but does not significantly affect throughput. No packet loss occurred in all scenarios. OSPF without STP had the lowest jitter at 0.011ms, and EIGRP with STP had the highest at 0.0124ms. This study shows that the choice of routing protocol and STP implementation affects IPv6 network performance, depending on throughput or delay priorities.